International Student Mobility and Turquality Perspective in Higher Education - Ali Kurt; Meriç Kılınç; Fevzi Rifat Ortaç (Üniversite Araştırmaları Dergisi)
Purpose: Today, the phenomenon of globalization that directly affects the developments in the world is changing and transforming Higher Education. Internationalization in higher education is one of the critical areas that many countries take into account and develop policies. Increasing the number of international students makes a wide range of contributions to countries. Economic, social, political, academic, and cultural policies are the main factors affecting student mobility. In this study, it is aimed to evaluate the effect of the Turquality program on international student mobility.Design/methodology/approach: In the study, data on international student mobility were evaluated.Findings: The United States and the United Kingdom, where the higher education system is highly developed, have the highest share in this area, with the contribution of their native language being English. However, the recent anti-globalization developments in these countries have led to a change in the trend of international student mobility, enabling other countries to gain new opportunities. Turkey, with the effect of instability in the hinterland of the country, has achieved a significant rise in the number of international students in recent years.Discussion: In this study, international student mobility that increases with globalization is analyzed; Turkey’s policy in this area and the opportunities provided by the Turquality project to the Higher Education sector are discussed.